Efficacy and its Predictors of Antiviral Therapy with Nucleos(T)Ide Analogs in Patients with Chronic Hepatitis B - T. H. Nguyen; L. Yu. Ilchenko; L. I. Melnikova; K. K. Kyuregyan; I. V. Gordeychuk (SINAPS LLC, 2024)
Background: Antiviral therapy with nucleos(t)ide analogs for chronic hepatitis B is aimed at preventing disease progression and the development of complications. However, current therapies do not allow elimination of hepatitis B virus, and long-term treatment is required to maintain clinical effect in most patients. In this regard, the study of associated factors with the efficacy of antiviral therapy of nucleos(t)ide analogs is actual.Aim: To evaluate efficacy and identify predictors of response to antiviral therapy with nucleos(t)ide analogs in patients with chronic hepatitis B.Materials and methods: This retrospective-prospective observational study included 71 patients with chronic hepatitis B who received nucleos(t)ide analogs at the Center for Diagnosis and Treatment of Chronic Viral Hepatitis from 2008 to 2023. The efficacy of antiviral therapy with nucleos(t)ide analogs was evaluated after 24, 48, and 96 weeks of drug intake. The prognostic factors associated with obtaining a virologic response after one year of antiviral therapy and with achieving a significant decrease in liver density by transient elastometry were examined. Results: The virologic and biochemical response rate increased as antiviral therapy continued, and after 96 weeks of taking nucleos(t)ide analogs was 92.6 %. Baseline viral load level was an independent prognostic factor for achieving aviremia after 48 weeks of antiviral therapy (p=0.022). HBsAg clearance was observed in 2 (2.8 %) patients, HBeAg clearance - in 5 HBeAg-positive patients. On nucleos(t)ide analogs treatment there was a significant decrease of liver fibrosis measured by transient elastometry, and a high level of transient elastometry at the beginning of antiviral therapy is a factor associated with a significant decrease in liver density (by 25 % or more) (p=0.022).Conclusion: Antiviral therapy with nucleos(t)ide analogs has demonstrated high efficacy in suppressing hepatitis B virus replication, normalizing aminotransferase activity, and reducing liver fibrosis. Baseline viral load and transient elastometry levels are the most important prognostic factors associated with the efficacy of antiviral therapy with nucleos(t)ide analogs.